SEMANTIC PECULARITIES OF COMPOUND WORDS IN CONTEXTS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This study explores the complex factors that shape the interpretation of compound words, with a particular focus on semantic transparency, idiomaticity, and the influence of context. By integrating insights from cognitive linguistic frameworks and employing corpus-based analytical methods, the research sheds light on how individual components of compound words interact to form holistic meanings. It emphasizes the dynamic and often non-linear relationship between a compound’s constituents and its overall semantic interpretation. Through a detailed examination of language use in authentic contexts, the study demonstrates that the understanding of compound words is not solely dependent on their morphological structure but is also significantly affected by idiomatic usage patterns and contextual cues. Ultimately, the findings contribute to a deeper understanding of how language users process and comprehend complex lexical constructions in real-world communication.